The banishment of Beverland: sex, sin, and scholarship in the seventeenth-century Dutch Republic - Hollewand, Karen Eline (Brill's studies in intellectual history, 2019)
Prologue: banishment (1650-1680) -- Sin -- Scripture -- Scholarship -- Sex -- Epilogue: exile (1680-1716)